2015
DOI: 10.1097/aog.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Opportunistic Salpingectomy as an Ovarian Cancer Prevention Strategy

Abstract: Salpingectomy with hysterectomy for benign conditions will reduce ovarian cancer risk at acceptable cost and is a cost-effective alternative to tubal ligation for sterilization. Opportunistic salpingectomy should be considered for all women undergoing these surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 39 publications
0
78
0
Order By: Relevance
“…Salpingectomy with delayed oophorectomy has been proposed as an alternative to RRSO in order to postpone the onset of premature menopause and its effect on non-cancer menopause-related morbidity and quality of life(116). Modeling of the cost-effectiveness of this approach demonstrated acceptability and a survey of previvors and key stakeholders demonstrated interest and acceptability of this approach (117, 118). Several prospective studies are in various phases of development and patient accrual (119, 120).…”
Section: Surgical Prevention For Women At High Risk Of Ovarian Cancermentioning
confidence: 97%
“…Salpingectomy with delayed oophorectomy has been proposed as an alternative to RRSO in order to postpone the onset of premature menopause and its effect on non-cancer menopause-related morbidity and quality of life(116). Modeling of the cost-effectiveness of this approach demonstrated acceptability and a survey of previvors and key stakeholders demonstrated interest and acceptability of this approach (117, 118). Several prospective studies are in various phases of development and patient accrual (119, 120).…”
Section: Surgical Prevention For Women At High Risk Of Ovarian Cancermentioning
confidence: 97%
“…Both of these statements were more conservative than the proposed plan of the British Columbia Ovarian Cancer Research Group program, instituted in 2010, which involved performing opportunistic salpingectomy with benign hysterectomy or in lieu of bilateral tubal ligation for permanent contraception. These authors suggested that this approach would yield a 20–40 percent population risk reduction for ovarian cancer over the next 20 years [14]. …”
Section: Fallopian Origin and Prevention Of Ovarian Cancermentioning
confidence: 99%
“…The estimated risk reduction for any individual person undergoing opportunistic salpingectomy is up to 50 percent [14]. Although this is an appreciable benefit, it must be tempered with a reminder that women at population risk of ovarian cancer have only a 1:70 or 1.4 percent lifetime risk [14].…”
Section: Fallopian Origin and Prevention Of Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…They estimated that use of BS in this fashion would reduce the risk of ovarian cancer by 38% and 29% when employed with hysterectomy or instead of tubal ligation, respectively (24). They conclude that “opportunistic salpingectomy should be considered for all women undergoing these surgical procedures.”…”
mentioning
confidence: 99%